2008
DOI: 10.1007/s00383-008-2301-y
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of exomphalos: an institutional experience

Abstract: Neonates with exomphalos minor have better survival, decreased LOS, time to full enteral feeds and shorter duration of mechanical ventilation. Syndromic associations were more common in exomphalos minor. Respiratory failure was the major cause of mortality in infants with exomphalos major.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 9 publications
2
24
1
2
Order By: Relevance
“…In infants with giant omphalocele, respiratory failure has been shown to be the major cause of mortality [5,17]. These infants have been shown to have a statistically longer length of stay and number of days on mechanical ventilation [6]. A higher incidence of respiratory failure, prolonged ventilatory support, abnormal pulmonary function testing in survivors, and need for tracheostomy have been described in many reports [5,9,14,23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In infants with giant omphalocele, respiratory failure has been shown to be the major cause of mortality [5,17]. These infants have been shown to have a statistically longer length of stay and number of days on mechanical ventilation [6]. A higher incidence of respiratory failure, prolonged ventilatory support, abnormal pulmonary function testing in survivors, and need for tracheostomy have been described in many reports [5,9,14,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Poor long-term outcomes for infants with omphalocele are more likely in the presence of associated structural or chromosomal abnormalities that occur in approximately 50-77% of these infants [2,3,4]. Other factors associated with poor outcomes include early respiratory distress [5], presence of liver within the omphalocele sac [6], high in utero omphalocele diameter to abdominal circumference ratio [7], low birth weight, low gestational age, and antenatal rupture of the sac [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Some studies have associated giant (defined as the presence of liver herniation) or ruptured omphalocele with respiratory insufficiency due to pulmonary hypoplasia [11,21], and recently, a decreased lung/thorax ratio and an increased chest/trunk length ratio were also associated with pulmonary hypoplasia and need for prolonged mechanical ventilation in fetuses with giant omphalocele [22]. In fact, 3-dimensional ultrasound has shown that lung volume in fetuses with abdominal wall defects is smaller compared to normal fetuses [23].…”
Section: Discussionmentioning
confidence: 99%
“…In a 10-year retrospective study of outcome of exomphalos in 52 infants (24 minor, 27 major), Vachharajani et al found a mortality rate of 33% in the major group and 8% in the minor group. 9 Exomphalos has chromosomal and syndromic associations, which may impact on the total LOS. The median LOS in the study by Vachharajani et al was 10 days for minor and 47 days for major exomphalos.…”
Section: Exomphalosmentioning
confidence: 99%